2016
DOI: 10.3233/wor-162427
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative job stress and ego aptitude in male scientific researchers

Abstract: Male researchers had higher levels of qualitative overload. Increasing supervisor support is essential in decreasing this qualitative overload. Furthermore, enhancement of nurturing parent ego aptitude (i.e., careful consideration for others) is also important for qualitative overload management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…There have been several reports concerning the research of egogram. For example, the subjects were obesity, anorexia nervosa, atopic dermatitis, white coat hypertension [11][12][13][14]. The characteristic point of these is that these diseases have been included in the psychosomatic disorders and that applying TEG would be beneficial and helpful for diagnosis, treatment, cure and care.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports concerning the research of egogram. For example, the subjects were obesity, anorexia nervosa, atopic dermatitis, white coat hypertension [11][12][13][14]. The characteristic point of these is that these diseases have been included in the psychosomatic disorders and that applying TEG would be beneficial and helpful for diagnosis, treatment, cure and care.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that this stressful state would be caused by a decrease in morality related to interpersonal relationship adjacent to NP decrease. [16] Along with the popularization of the internet worldwide, desiring information can be obtained instantly and easily. As a result, people have tendency not to think deeply, inducing a decreased level of factor A.…”
Section: Discussionmentioning
confidence: 99%
“…Job demands generally fall into two broad categories: quantitative workload (the amount and speed of work) and qualitative workload (cognitive, mental, and emotional efforts pertaining to the difficulty of tasks and an individual's capabilities) ( 28 ). Studies have reported that quantitative and qualitative workloads are associated with various mental problems among workers ( 29 31 ). Job control, the other stress factor in the JDC model, has also been reported to have a strong impact on an individual's perceived occupational stress ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%